1965
DOI: 10.1111/j.1476-5381.1965.tb01742.x
|View full text |Cite
|
Sign up to set email alerts
|

The Tachyphylaxis Caused by Mephentermine and Tyramine

Abstract: The sympathomimetic action of mephentermine, like that of tyramine, is considerably reduced by procedures that deplete noradrenaline stores, such as administration of reserpine. We have, however, observed important differences between these two sympathomimetic amines in the speed with which tachyphylaxis to the pressor action develops, in their behaviour in dogs treated with reserpine before and after infusions of noradrenaline and in their action on the heart-lung preparation. Blaschko (1962) and Day & Rand (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

1966
1966
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The indirectly acting sympathomimetic amine has to be injected during the noradrenaline infusion (0.5 Pg/kg/min) but not after. In contrast to the situation in the normal animal (Fawaz & Simaan, 1965), consecutive injections of tyramine result in no diminution of the pressor response as long as the noradrenaline infusion continues. The pressor action of mephentermine is also restored but only for the first dose, the second dose being very slightly effective.…”
mentioning
confidence: 56%
See 3 more Smart Citations
“…The indirectly acting sympathomimetic amine has to be injected during the noradrenaline infusion (0.5 Pg/kg/min) but not after. In contrast to the situation in the normal animal (Fawaz & Simaan, 1965), consecutive injections of tyramine result in no diminution of the pressor response as long as the noradrenaline infusion continues. The pressor action of mephentermine is also restored but only for the first dose, the second dose being very slightly effective.…”
mentioning
confidence: 56%
“…In a previous publication (Fawaz & Simaan, 1965) we postulated the presence in nonreserpinized animals of a large store from which noradrenaline can be released by tyramine and a "small" store from which noradrenaline can be released by tyramine or mephentermine. The small store, equivalent to that described by Burn & Rand (1958), but apparently not the large store, is the one that is repleted in a reserpinized animal after the acute infusion of excess noradrenaline.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Eble and Rudzik [1965], Bhagat [1965] and Dag [1967] suggested that the lack of crossed tachyphylaxis be tween tyramine and the alpha methylated amines could be ex plained by the different mechanisms of norepinephrine releasing action of the drugs. According to Blaschko [1962] and Day and Rand [1963], it was proposed by Fawas and Simaan [1965] that the alpha methylated sympathomimetic amines first release nor epinephrine from the stores and then block their own entry, as well as, that of subsequent doses of other indirectly acting amines into the stores. Rudzik [1965), Bhagat [1965] and Day [1967], The lack of crossed tachyphylaxis between tyramine, a non-alpha methylated amine, and the alpha methylated amines, in the animal not pretreated with MAO inhibitor suggest an action of the drugs on two different, functionally connected, storage sites of the adrenergic transmitter.…”
Section: Discussionmentioning
confidence: 99%